2022
DOI: 10.3390/healthcare10020315
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping the Healthcare Sector with Economic Policy Measures Based on COVID-19 Epidemic Severity: A Global Study

Abstract: Governments around the world are looking for ways to manage economic consequences of COVID-19 and promote economic development. The aim of this study is to identify the areas where the application of economic policy measures would enhance the resilience of societies on epidemic risks. We use data on the COVID-19 pandemic outcome in a large number of countries. With the estimation of multiple econometric models, we identify areas being a reasonable choice for economic policy intervention. It was found that viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…One study pointed to the era of big data and the necessity of publicizing health education and health literacy in a targeted way to meet the public's needs and to understand how the public's demand for subjects, contents, and forms of health literacy service change in some situations such as the era of COVID-19 [33]. In the context of macroeconomics, AI helps identify innovative economic policy measures that can be applied before an epidemic [34]. Another study reported that AI, as a new way of exploring the social context, can minimize decision-making bias and improve the effectiveness of messages [35].…”
Section: Discussionmentioning
confidence: 99%
“…One study pointed to the era of big data and the necessity of publicizing health education and health literacy in a targeted way to meet the public's needs and to understand how the public's demand for subjects, contents, and forms of health literacy service change in some situations such as the era of COVID-19 [33]. In the context of macroeconomics, AI helps identify innovative economic policy measures that can be applied before an epidemic [34]. Another study reported that AI, as a new way of exploring the social context, can minimize decision-making bias and improve the effectiveness of messages [35].…”
Section: Discussionmentioning
confidence: 99%
“…This situation and other socioeconomic factors (as discussed above) prevent them from seeking medical treatment. Prevention programs and policy measures to control the spread of COVID-19 should target all people from the lower and middle classes, and young people from the higher class [13] in order to boost resilience of communities [5].…”
Section: Discussionmentioning
confidence: 99%
“…A large body of researchhas analysed the short-term and long-term economic impacts of COVID-19 [4][5][6]. The findings of the studies suggest that the pandemic has had serious negative impacts on households [7] as well as regional [8] and global [9] economies.…”
Section: Introductionmentioning
confidence: 99%
“…Since GDP (Gross Domestic Product) is a key indicator of market-related economic activities in a country, we use provincial GDP per capita to estimate provincial socioeconomic developments ( 51 ). Since business activities (design, production, and technical marketing) require provincial government regulation as a guide ( 38 , 39 ), the food producers constitute a source of pressure upon government for impartial legal innovation of regulations. The business activities of food industries can be indicated by Food Industry Sales Value (FISV).…”
Section: Methods and Data Analysismentioning
confidence: 99%
“…As the main body for adjusting the standard filing policy of food safety firms, the amount and size of the food industry have an important influence on the requirements for standard filing policies and also constitute a source of pressure when supervisory authorities oversee them. As the number of food producers increases, so does the number of business activities (design, production, and technical marketing) that require provincial government regulation as a guide to facilitate governmental structures ( 38 , 39 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%